The Implementation of Green Leadership by the School Principal in Developing a Nature-Based School - Sulaiman , Muhammad Arib; Putra, Eka; Zebua, Ali Marzuki (Thawalib: Jurnal Kependidikan Islam, 2025)
Nature-based education shapes environmentally conscious generations through a sustainable curriculum, eco-friendly technology, community involvement, and visionary, transformative green leadership. This study analyzes the principal's implementation of Green Leadership in developing a nature-based school at Sekolah Alam Insan Rabbani, Sungai Penuh City. The study employs a qualitative case study approach, using observation, semi-structured interviews, and document analysis as data collection methods. Data processing includes condensation, data display, and conclusion drawing, with triangulation used as a data validity technique. The research findings show that: (1) Integrating the principal’s Green Leadership roles as educator, administrator, innovator, and motivator successfully promotes a culture of sustainability through exemplary behaviour, zero-waste policies, green curriculum integration, and active participation in environmental activities and community education. (2) The principal's development of a nature-based school involves integrating environmental literacy, implementing a nature-based curriculum, promoting zero-waste programs, and empowering the school and local communities through active learning, ecological activities, and ongoing synergy between the school and its surrounding environment. Conclusion: The principal plays a strategic role in integrating a green school approach through curriculum, culture, policies, environmental programs, collaboration, and capacity-building of the school community.